Gastrointestinal Parasites Amongst Epileptic and Non-Epileptic: Prevalence and Associated Risk Factors of Gastrointestinal Parasites Amongst Epileptic and Non-Epileptic Individuals in Batibo Subdivision, Northwest Region of Cameroon: A Community-Based Cross-Sectional Survey - Bih, Mbah Sylvie (British Journal of Healthcare and Medical Research, 2024)
The aim of this study was to investigate the prevalence of gastrointestinal parasites and establish the relationship between the prevalence of these parasites and epilepsies amongst the population and associated risk factors. This cross-sectional survey was carried out in Batibo Health District from April 2021 to July 2021. A total of 402 stool samples were collected and examined using the Formol-Ether concentration technique to detect the presence of helminth eggs. A well-structured and pretested questionnaire was administered to collect socio-demographic data and to assess the risk factors. Data was analyzed using SPSS vs 23. P values ≤0.05 were considered significant. Ages ranged from 3-72 years and the highest number of participants were females 275(68.4%). Results obtained showed that the overall prevalence of persons with intestinal helminths was 12.4% (50/402). Taenia spp was the most prevalent parasite 4.2% (17/402) followed by Ascaris lumbricoides 4.0% (16/402), Entamoeba coli 3.0% (12/402) and the least prevalent species was Ancylostoma/Necator spp, 2.2% (09/402). Two participants (0.5%) each had multiple infections with Ascaris /E coli and Ascaris/hookworm infection. Parasitic infections were significantly higher in participants of age group 15-24 years (29.5%; p= 0.0001), and insignificantly higher in females (13.5%; p=0.363) and students (32.1%; p=0.070). Parasitic infections were also significantly (p=0.004) higher in epileptic participants 34.04% (16/47) who were more infected with Taenia spp 17.02% (8/47). Multivariate analyses showed significant predisposing social factors of intestinal parasites identified in this study such as source of water (boreholes, 0.041 and streams, 0.018), frequency of deworming (twice yearly, 0.043), lack of latrines (0.034) and geophagia (0.023). Multivariate analyses also showed that the use of boreholes 2.815(0.849-9.3), streams 4.329 (1.29-14.5), deworming once in six months 0.28 (0.08-0.98), geophagia participants 1.02 (1.24-10.45) and participants who eat pork or beef 0.034 (0.58-1.0) were risk factors for the development of intestinal parasites. Thus, the prevalence of gastrointestinal parasites has increased considerably over the years although the rate is not alarming.